(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
massive amount of solid garbage generated across world is a serious biological & technical issue. Vermicomposting might be feasible solution for ecologically friendly solid waste management. This article gives a broad overview of potential of vermicomposting as an environmentally beneficial method. Better results are obtained by combining composting & vermicomposting procedures. Furrmore, digestion of organic wastes improves chance for both microbes & earthworm for transforming organic portion of solid waste under regulated environmental circumstances, which helps for enhancing vermicomposting procedure. By extrapolation, main variables that impact vermicomposting process appear to include feeding, stocking density, pH, C/N ratio, temperature, & moisture. Furrmore, nutrient-rich compost produced by vermicomposting might be utilised to generate biogas. As a result, solid waste management & energy generation may both be accomplished at same time at no additional expense. Vermiculture is environmentally friendly because earthworms eat anything biodegradable, & vermicomposting helps with garbage disposal. refore use of vermicomposting is expected to be high in future increasing efficiency of earthworms in agriculture.